Implementasi Model Cox Stratifikasi Interaksi dan Tanpa Interaksi untuk Mengidentifikasi Faktor-Faktor Laju Kesembuhan Pasien TB Paru - Fakhira Modeong; Dewi Rahmawaty Isa; Ismail Djakaria; Muhammad Rezky Friesta Payu; Sri Lestari Mahmud (Research in the Mathematical and Natural Sciences, 2023)
This study aims to determine the factors that most influence the rate of recovery of pulmonary tuberculosis patients using the Cox Proportional Hazard model. In the case of the cure rate of pulmonary tuberculosis patients, not all independent variables meet the proportional hazard assumption, so the stratified cox regression model is used. The stratified cox regression model used is the stratified cox model with interaction and without interaction involving pulmonary tuberculosis patients in one of the Gorontalo Hospitals. The results showed that the variables of shortness of breath, previous pulmonary tuberculosis patients, and smoking habits were the most significant factors affecting the recovery rate of pulmonary tuberculosis patients.